1997
DOI: 10.1017/s0033291797004807
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychiatric disorders on work loss days

Abstract: The results reported here suggest that work impairment is one of the adverse consequences of psychiatric disorders. The current policy debate concerning insurance coverage for mental disorders needs to take these consequences into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
364
2
13

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 602 publications
(398 citation statements)
references
References 51 publications
(50 reference statements)
19
364
2
13
Order By: Relevance
“…However, at the same time, these figures compare reasonably well with the prevalence of depressive and anxiety disorders reported in other studies using psychiatric interviews. The prevalence of major depressive disorder in working people is reported to be 2.3% by Kouzis and Eaton (1994) and 4.4% by Kessler and Frank (1997). Interestingly, in other studies, the prevalence of depressive symptoms is reported to be as high as 16.5-25.7% in occupational samples (Lexis et al 2009;Niedhammer et al 1998).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, at the same time, these figures compare reasonably well with the prevalence of depressive and anxiety disorders reported in other studies using psychiatric interviews. The prevalence of major depressive disorder in working people is reported to be 2.3% by Kouzis and Eaton (1994) and 4.4% by Kessler and Frank (1997). Interestingly, in other studies, the prevalence of depressive symptoms is reported to be as high as 16.5-25.7% in occupational samples (Lexis et al 2009;Niedhammer et al 1998).…”
Section: Discussionmentioning
confidence: 88%
“…Some studies looked at interview-based psychiatric disorders (Kessler and Frank 1997;Dewa and Lin 2000;Kouzis and Eaton 1994;Suija et al 2009;Kruijshaar et al 2003;Broadhead et al 1990;Jenkins 1985;Laitinen-Krispijn and Bijl 2000), others at questionnaire-based psychological symptoms (Hilton et al 2008;Bültmann et al 2005Bültmann et al , 2006Virtanen et al 2007;Kivimäki et al 2001;Bourbonnais and Mondor 2001;Andrea et al 2003;Väänänen et al 2003; Lexis et al 2009;Duijts et al 2006;Eriksen et al 2003;Janssen et al 2003;Ahola et al 2008;Borritz et al 2006;Kivimäki et al 2007;Krantz and Ostergren 2002). The symptom predictors studied were distress (Hilton et al 2008;Bültmann et al 2005;Virtanen et al 2007;Kivimäki et al 2001;Bourbonnais and Mondor 2001;Andrea et al 2003;Väänänen et al 2003), depression (Bültmann et al 2006; Lexis et al 2009;Duijts et al 2006;Eriksen et al 2003), fatigue (Bültmann et al 2005;Andrea et al 2003;Duijts et al 2006;Eriksen et al 2003;…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, recent surveys in the United Kingdom indicate that between 25% and 40% of workers in various occupational groups could be diagnosed with a minor psychiatric disorder (Hardy, Woods, & Wall, 2003;Stride, Wall, & Catley, 2007). Similarly, studies of the United States workforce suggest an average 30-day workplace prevalence of 18% for any DSM psychiatric disorder (Kessler & Frank, 1997).…”
Section: Introductionmentioning
confidence: 99%